The newly developed of blockchain architecture on zakat collection in Malaysia: a case in MAIWP-PPZ, Malaysia - Khairi, Khairil Faizal; Laili, Nur Hidayah; Ahmad, Azuan (2023)
This study concentrates on the integration of blockchain technology into the existing zakat management framework in Malaysia, specifically within the PPZ-MAIWP context. The introduction of blockchain technology offers a promising avenue for revitalizing zakat institutions. It enables real-time tracking, monitoring, reporting, and verification of zakat fund utilization, facilitating a comprehensive assessment of its impact and promoting strong governance within these institutions. The research methodology employed for developing the blockchain architecture for zakat collection within PPZ-MAIWP consists of three distinct stages which are assessing the existing of manual standard operating procedure (SOP) on zakat collection, the interview sessions with officer in PPZ-MAIWP for digitalization of current SOP and the development of zakat collection blockchain architecture. The implementation of blockchain technology, in conjunction with smart contracts, empowers zakat institutions to actively contribute to the economic development of Malaysia and the broader Muslim world. While still in its early stages in the Malaysian Islamic social finance sector, blockchain has already demonstrated its potential to reshape the global financial landscape. The study suggests that integrating blockchain technology into zakat management has far-reaching implications for improving the effectiveness, transparency, and fairness of zakat collection processes, ultimately contributing to the socio-economic development of Muslim communities while promoting the sustainable development goals (SDGs). Additionally, it highlights the transformative potential of blockchain technology in the broader financial domain. The practical implications of integrating blockchain technology into zakat management are multifaceted. They encompass improved collection and distribution, enhanced donor confidence, fairness in fund allocation, efficient monitoring and reporting, comprehensive impact assessments, strong governance, contributions to economic development, and the potential to reshape global finance. These implications collectively contribute to the revitalization of zakat institutions and the advancement of socioeconomic equality within Muslim communities. The study's originality stems from its innovative approach to zakat management by integrating blockchain and smart contracts, its focus on financial inclusion and equality, its emphasis on real-time tracking and comprehensive impact assessment, and its recognition of the global implications of blockchain adoption in zakat management.